Persepsi Pengunjung Terhadap Keberadaan Motor Kecil (Mocil) di Tugu Sirih Kota Tanjungpinang - Agustina Agustina; Nanik Rahmawati; Rahma Syafitri (Universitas Sains dan Teknologi Komputer, 2023)
Every individual always needs space as a place for them to be able to interact with each other. Therefore, people need public space as a place for them to meet their needs both in terms of social, cultural and economic. Like Tanjungpinang, it provides many public spaces, one of which is the Tugu Sirih. Tugu Sirih is a public space that can be enjoyed free of charge by the public. There are various kinds of food and game entertainment offered there, one of which is small motorbike (mocil). Mocil is a game that is usually played by children but can also be used by adults. However, the existence of a car being played in the Tugu Sirih area has caused anxiety for the community. The visitor community feels disturbed by the noise generated from the motorbike and the way the motorbike is driven, which often speeds up, makes visitors feel worried when they are in the Tugu Sirih area, this has also become a topic of conversation for the community on social media. The purpose of this study is to describe visitors' perceptions of the existence of a car at Tugu Sirih, Tanjungpinang city. The method used in this study is a descriptive-qualitative research method with a total of 8 informants. The informant determination technique used in this study was a purposive sampling technique. Data collection techniques in this study through observation and interviews. The results of this study indicate that visitors feel disturbed by the presence of motorbikes at Tugu Sirih. This is because the noise produced by the mocil disturbs the sense of hearing. Small motorbikes are driven recklessly by children without clear track directions. In addition, this small motorbike is played by children without using safety equipment.